The Impact of Monopoly Pricing on the Lerner Symmetry Theorem: Reply - Ray, Edward John (Quarterly Journal of Economics, 1983)
Journal Article The Impact of Monopoly Pricing on the Lerner Symmetry Theorem: Reply Get access Edward John Ray Edward John Ray Ohio State University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 98, Issue 3, August 1983, Pages 535–537, https://doi.org/10.2307/1886027 Published: 01 August 1983